Populist and nativist attitudes: Does ingroup-outgroup thinking spill over across domains?. (June 2021) - Rooduijn, Matthijs; Bonikowski, Bart; Parlevliet, Jante
What are the attitudinal consequences of the growing pervasiveness of populism and nativism? We conceive of both populism and nativism as binary moral frameworks predicated on an antagonistic relationship between 'us' and 'them'. Our study investigates the presence of spillover effects between these two forms of ingroup-outgroup thinking among survey respondents in the Netherlands. We posit that exposure to populist (nativist) messages fuels nativism (populism), but only among those positively predisposed toward these messages in the first place. A first survey experiment, focusing on antipathies toward refugees and Muslim immigrants, confirms the former expectation, but a second experiment calls into question the latter hypothesis. Moreover, the second experiment does not replicate the effects of populist message exposure on general immigration attitudes. We discuss several possible reasons for these mixed results.